QUANTIFYING LAND USE/COVER CHANGE AND LANDSCAPE FRAGMENTATION IN DANANG CITY, VIETNAM: 1979–2009 - N. H. K. Linh; S. Erasmi; M. Kappas (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
Studying temporal changes of land use and land cover (LULC) from satellite images has been conducted in Vietnam several years. However, few studies have been done to consider seriously the relationship between LULC changes and the fragmentation of landscape. Hence, analysing the changes of LULC and landscape pattern helps revealing the interactions between anthropogenic factors and the environment, through which planning actions could be effectively supported. The present study aimed to examine these changes in the surroundings of Danang City, Vietnam from 1979 to 2009 based on Landsat Multi-Spectral Scanner (MSS), Landsat Enhanced Thematic Mapper Plus (ETM+) and ASTER satellite images. The Multivariate Alteration Detection (MAD) approach was employed for processing and postclassification change detection, from which key landscape indices were applied by using FRAGSTATS. The results showed that during the whole study period, there was a notable decrease of forestland, shrub, agriculture and barren while urban areas expanded dramatically. Further spatial analysis by using landscape metrics underlined the evidence of changes in landscape characteristics with an increase in total number of patches and patch density while the mean patch area decreased during the span of 30 years. Consequently, the landscape structure of Danang city became more fragmented and heterogeneous.